The Effect of Inflation on the Yield of Fixed Income Securities: Evidence from Chinese Securities Market - Zhu, Yanxu (2020)
Inflation has become a very common economic phenomenon in today's society, its impact on the social economy is always concerned, and the relationship between inflation and fixed income securities market is also a hot issue of finance. One of the more obvious characteristics of fixed income securities is that, in general, this kind of securities has relatively clear cash inflows, so if the price changes are not considered, the rate of return of fixed income securities is stable. But this kind of stability is the stability of the nominal yield, after considering inflation, the yield of fixed income securities is not stable. Inflation risk is a systemic risk, as long as the securities in the fixed income securities market will face this risk. When the economy is relatively healthy and stable, fixed income securities can be priced to ignore this risk and only need to be compensated at the general level of interest rates. But in times of economic uncertainty, especially in recent years, global inflation has been relatively high compared with long-term historical data, so inflationary pressures cannot be ignored. At present, central banks in major western developed countries and regions are implementing intensive monetary easing policies in response to the negative impact of COVID-19 on the economy. There is concerned by people from all walks of life that such policies will lead to global inflation. At present, there are many studies on the effect of inflation on the stock market, but few studies and empirical analyses on the effect of inflation on the fixed income securities market. China's fixed income securities market is gradually developing, so in this dissertation, I will take the Chinese market as an example to study the relationship between inflation and the rate of return of fixed income securities and the extent to which inflation affects the rate of return of fixed income securities with different maturity structures.